An investigation of football player movement skills at the stage of their sport improvement - Valeriy Marchenko; Igor Marchenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: theoretical and experimental substantiation of methodology of improving movement skills football players of 16-18 years at the stage of sports perfection Material & Methods: theoretical analysis and generalization of experience of leading trainers and scientists, pedagogical observations, pedagogical experiment, pedagogical control testing, digital video, physiological, medical and biological and physiological methods, pedagogical programming method, mathematical methods of statistics. Results: implemented programming the movement activity of football players of 16-18 years at a stage of sports perfection. Conclusion the results showed both positive and negative trends in the course of the training process Using the method of pedagogical testing in the process of entrance control, in our opinion, is also effective, which was shown by the research.